Bridging Education and Industry for Enhanced Corporate Competency and Economic Development - Sajjad Hussain; Iftikhar Hussain; Muhammad Ismail Nasir; Sehrish Munaf (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study aims to address the disconnect between academic programs in business education and the practical needs of the industry in Pakistan, advocating for a curriculum redesign that better aligns with industry demands. Using thematic analysis, the research identifies key themes that shed light on the nature of this gap and offers targeted recommendations. The analysis delves into various dimensions, such as perceptions of business studies and the observed industry gap, to explore how both sectors view the existing curriculum's effectiveness in preparing graduates for the workforce. The research also emphasizes the gap between theoretical knowledge imparted in academic settings and the practical skills demanded by employers. Key areas of focus include how cultural adaptability and adjustment issues influence graduates' transition from academia to the workplace and how curriculum content can be better tailored to meet industry expectations. By mapping out these themes, the study provides insights into ways of aligning academic knowledge with practical skills, proposing adjustments that might make the curriculum more responsive to real-world business practices. Additionally, the study discusses the need to enhance cultural adaptability among graduates to help them better integrate into diverse workplace environments. It also highlights the importance of aligning theoretical instruction with practical applications to close the gap between academic instruction and industry needs. The findings serve as a guide for curriculum planners, educators, and policymakers, offering actionable recommendations to improve the synergy between academia and industry, ultimately equipping graduates with the skills required for the business sector.